2012
DOI: 10.1001/archneurol.2011.2956
|View full text |Cite
|
Sign up to set email alerts
|

Anti–Myelin Oligodendrocyte Glycoprotein Antibodies in Pediatric Patients With Optic Neuritis

Abstract: To study the humoral immune response directed at myelin oligodendrocyte glycoprotein (MOG) in pediatric patients with isolated and recurrent optic neuritis (ON).Design: Observational prospective case series.Setting: Six pediatric hospitals in Germany and Austria.Patients: Thirty-seven patients 18 years or younger with single or recurrent episodes of ON were recruited from 6 different hospitals.Main Outcome Measures: Clinical features, magnetic resonance imaging findings, intrathecal IgG synthesis, and outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
132
2
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(144 citation statements)
references
References 17 publications
(29 reference statements)
4
132
2
6
Order By: Relevance
“…Furthermore, high MOG-Ab titre has been detected predominantly in patients with recurrent ON. 7 We have previously reported that concomitant presence of MOG-Abs in AQP4-Ab seropositive optic neuritis is associated with severe visual function impairment. However, MOG-Ab seropositive optic neuritis has not been elucidated using new methods such as cell-based assay.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, high MOG-Ab titre has been detected predominantly in patients with recurrent ON. 7 We have previously reported that concomitant presence of MOG-Abs in AQP4-Ab seropositive optic neuritis is associated with severe visual function impairment. However, MOG-Ab seropositive optic neuritis has not been elucidated using new methods such as cell-based assay.…”
Section: Introductionmentioning
confidence: 92%
“…5 Recent studies have shown that among AQP4-Ab seronegative ON cases with relatively good prognosis but repeated relapses, some are seropositive for myelin oligodendrocyte glycoprotein (MOG) antibodies. 6,7 In addition, MOG is known to be a causative protein of experimental autoimmune encephalitis (EAE). 8 MOG derived from oligodendrocytes induces ON in mouse, suggesting that MOG antigen may be a cause of multiple sclerosisassociated ON.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] In contrast, the clinical relevance of MOG antibodies in adults is unclear, as only a minority of patients with MS and NMO/NMOSD are seropositive. 16,[18][19][20][21][22][23][24] Herein, we provide evidence that MOG antibodies are a clinical biomarker of bilateral and/ or recurrent optic neuritis (BON) in adults and describe the characteristic clinical course, response to therapy, and visual outcomes of this condition.…”
mentioning
confidence: 99%
“…23,24 The presence of relapses has been observed in pediatric patients with MOG antibodies and LETM or recurrent or bilateral ON. 15,21 Notably, a number of our MOG antibody-positive patients had previous treatment with short courses of pulsed steroids alone and had a propensity to relapse. This may indicate that early and sustained immunotherapy with multiple agents, including steroidsparing maintenance immunosuppression, may be more effective in maintaining disease remission.…”
mentioning
confidence: 99%
“…A study on 37 cases, 18 or under 18 years old with recurrent or single episodes of optic neuritis, suggested that generally these patients had high titer serum anti-MOG antibodies from the subclass of IgG, especially in patients suffering from recurrent episodes of optic neuritis (31). In a group of pediatrics suffering from recurrent or monophasic ADEM, optic neuritis was diagnosed.…”
Section: Anti-mog Antibodies In Optic Neuritismentioning
confidence: 99%